Tamkin Sempurna as a Condition for Exemption from Obligations Husband to Wife - Khatimah, Husnul; Rahim, Raisa; AD, Muhammad Irfan; Al Latifa, Soraya; Shafia, Aqila (Jurnal Mediasas: Media Ilmu Syari’ah dan Ahwal Al-Syakhsiyyah, 2023)
In Indonesia, the rights and obligations of husband and wife are regulated in Law No.1 of 1974 concerning Marriage and the Compilation of Islamic Law (KHI), but in KHI Article 80 paragraph 5, states that the husband’s obligations towards his wife as mentioned in paragraph (4) letters a and b above come into effect after the perfect tamkin of his wife. This statement states that before the perfect tamkin the obligation to provide for a husband can be waived. This study aims to explore the exemption of the husband’s obligation to his wife in the presence of Perfect Tamkin. The type of research used is normative research with a normative juridical approach. The results of the discussion of Imam Ash-Shafi’i provide exemption from the obligation of a husband to his wife required in the Perfect Tamkin in two circumstances, namely, the first situation when a man marries a woman who is still small (not yet baligh) / not yet worthy of intercourse. Secondly, the exemption of the obligation to provide maintenance by the husband towards the wife also applies when a wife refuses to be intimate, without reasons such as illness or menstruation, then the husband is exempted from the obligation to provide maintenance until the wife is willing to be intimate again. That way in these two circumstances, according to the view of Imam Asy-Shafi’i, the husband can be relieved of the obligation to provide maintenance for a wife, this is in accordance with Article 80 paragraph (5) KHI. [Di Indonesia hak dan kewajiban suami istri diatur dalam Undang-Undang No.1 Tahun 1974 tentang Perkawinan dan Kompilasi Hukum Islam (KHI), namun dalam KHI Pasal 80 ayat 5, menyatakan bahwa Kewajiban suami terhadap istrinya seperti tersebut pada ayat (4) huruf a dan b di atas mulai berlaku sesudah ada tamkin sempurna dari istrinya. Pernyataan tersebut menyatakan bahwa sebelum adanya tamkin sempurna kewajiban menfakahi bagi seorang suami dapat dibebaskan. Penelitian ini bertujuan untuk menggali tentang pembebasan kewajiban suami terhadap istri dengan adanya Tamkin Sempurna. Jenis penelitian yang digunakan adalah penelitian normatif dengan pendekatan yuridis normatif. Hasil Pembahasan Imam Asy-Syafi’i memberikan pembebasan kewajiban seorang suami terhadap istri disyaratkan pada Tamkin Sempurna dalam dua keadaan yaitu, pertama keadaan ketika seorang laki-laki menikahi seorang perempuan masih kecil (belum baligh)/belum layak digauli. Kedua pembebasan kewajiban membarikan nafkah oleh suami terhadap istri juga berlaku ketika seorang istri yang menolak untuk digauli, tanpa alasan seperti sakit atau sedang haid, maka suami dibebaskan dari kewajiban memberikan nafkah sampai seorang istri mau untuk digauli kembali. Dengan begitu dalam dua keadaan ini menurut pandangan Imam Asy-Syafi’i suami dapat dibebeskan dari kewajiban memberikan nafkah terhadap seorang istri hal ini sesuai dengan Pasal 80 ayat (5) KHI.]